Motivational and Psychological Determinants of Students' Psychological Safety Depending on Birth Order - Papoyan, Varduhi; Galstyan, Alina (Bulletin of Yerevan University E: Philosophy, Psychology, 2026)
The article examines psychological safety as one of the key preconditions for positive personality development. It encompasses not only the individual’s subjective experiences and life history but also the systems of activity within which a person functions, learns, and develops while striving for self-realization.The study of students’ psychological safety requires consideration of factors related to the higher education system, which serves as an environment facilitating learning and socialization.Within the framework of this research, particular attention is given to the relationships between components of psychological safety, hardiness, and motivational characteristics of students, both in the educational process and in relation to birth order within the family. This factor significantly influences the development of basic trust in the world, self-confidence, and overall personality formation.The findings reveal statistically significant differences in psychological safety and motivational indicators among students depending on their birth order position within the family. Significant differences were found between the scores of only children and siblings. Older children demonstrated higher levels of resilience and responsibility, reflecting their family background and early family interactions. Single children were characterized by higher motivation scores, while younger siblings had lower scores on some parameters, highlighting their desire for psychological comfort. For all participants, the "Family" component, closely linked to emotional well-being and personal stability, plays a special role in the psychological security construct.
Keywords: psychological safety; students; motivation; hardiness; personality develop-ment; birth order